Effect of dietary xanthophyll level on body colour of goldfish (Carassius auratus) - LENG Xiang-jun; SHI Ying; LI Xiao-qin; XU Hai-hua; YANG Zhi-gang (浙江大学学报. 农业与生命科学版)
To investigate the effect of adding xanthophyll in diet on body colour of goldfish, six diets added with xanthophyll of 0 (control group), 50, 100, 150, 200, or 300 mg·kg-1 were prepared, and fed to goldfish with initial body mass of (7.8±0.3) g for 10 weeks. A colorimeter (WSC-S) was chose to determine values of three primary colours of body color of goldfish. The results showed that there was no significant effect of additional xanthophyll on growth of goldfish, but feed conversion ratio (FCR) was increased (P<0.05) by the additional xanthophyll of 300 mg·kg-1, compared with control group. In the respect of body colour, + a* value (redness) was increased, and L* value (luminance) was decreased by xanthophyll addition from 0 to 150 mg·kg-1. When the addition level of xanthophyll was higher than 150 mg·kg-1, +a* value and L* value kept constant. The +b* value (yellowness) of body surface was increased by additional xanthophyll of 200 mg·kg-1 or 300 mg·kg-1. With the increase of xanthophyll addition in diet, xanthophyll contents in skin, scale, muscle and tail fin were also increased. While the additional xanthophyll content was 150 mg·kg-1, goldfish had the highest content of xanthophyll in these tissues. Serum tyrosinase activity was significantly increased by the additional xanthophyll of 100, 150, 200, or 300 mg·kg-1. Results above show that the optimal xanthophyll addition in diet for goldfish pigmentation is 150 mg·kg-1.